Genome-Wide Identification and Capsaicinoid Biosynthesis-Related Expression Analysis of the R2R3-MYB Gene Family in Capsicum annuum L. - Wang, Jin; Liu, Yi; Tang, Bingqian; Dai, Xiongze; Xie, Lingling; Liu, Feng; Zou, Xuexiao (Frontiers in Genetics, 2020)
Capsaicinoids are naturally specialized metabolites in pepper and are the main reason that Capsicum fruits have a pungent smell. During the synthesis of capsaicin, MYB transcription factors play key regulatory roles. In particular, R2R3-MYB subfamily genes are the most important members of the MYB family and are critical candidate factors in capsaicinoid biosynthesis. The 108 R2R3-MYB genes in pepper were identified in this study and all are shown to have two highly conserved MYB binding domains. Phylogenetic and structural analyses clustered CaR2R3-MYB genes into seven groups. Interspecies collinearity analysis found that the R2R3-MYB family contains 16 duplicated gene pairs and the highest gene density is on chromosome 00 and 03. The expression levels of CaR2R3-MYB differentially expressed genes (DEGs) and capsaicinoid-biosynthetic genes (CBGs) in fruit development stages were obtained via RNA-seq and qRT-PCR. Co-expression analyses reveal that highly expressed CaR2R3-MYB genes are co-expressed with CBGs during early stages of pericarp and placenta development processes. It is speculated that six candidate CaR2R3-MYB genes are involved in regulating the synthesis of capsaicin and dihydrocapsaicin. This study is the first systematic analysis of the CaR2R3-MYB gene family and provided references for studying their molecular functions. At the same time, these results also laid the foundation for further research on the capsaicin characteristics of CaR2R3-MYB genes in pepper.